Working Within a Perfect Storm: The Current UK Care Crisis in Community Neurorehabilitation - Alyson Norman; Mark Holloway; Jackie Dean; Andrew Patterson; Ben Needham-Holmes; Valentina Curro; Craig Andrews; Phillipa Feltham-White; Jo Clark-Wilson (Journal of Long-Term Care)
Context: Within the UK, there is a shortage of support workers required to meet the needs of individuals with acquired brain injuries who often require extensive care packages.